Peace and justice in the community - Abdul Hak, Nora (2019)
IIUM is repositioning itself in this initial duration of 2019 - 2020 and the 17 Sustainable Development Goals (SDGs) of the United Nation (UN) will serve as a guide to all activities undertaken by the Kulliyyahs. Aligning with this new direction, AIKOL has taken initiative to introduce these strategic efforts through Kulliyyah’s programmes and activities with IIUM community and community in Gombak.